Analisis Cerita Pendek â€œDer TÃ¤nzer Maligeâ€ Karya Johannes Bobrowski - Rosnaini, Rosnaini; Dalle, Ambo; Rijal, Syamsu (Universitas Negeri Makassar, 2021)
The type of this research is descriptive qualitative. The purpose of this research is to describing theme, characters, plor, setting, message, and point of view in the short story â€œDer TÃ¤nzer Maligeâ€ by Johannes Bobrowski. The data in this study were obtained from reading the short story â€œDer TÃ¤nzer Maligeâ€ by Johannes Bobrowski. Data collection using library techniques, which are in the from of reading and notes technique on the object of research. The results of this study are as follws, a description of the theme elements: soldiers, character elements: main characters and extras, plot elements: mixed plot, background elements: place setting (village and army barracks) and time setting (August 1939 at the end of the season. Heat), the element of mandate: a high social Â spirit, the element of perspective: the third person point of view (Er).the interrelationship between the intrinsic elements of the short story, where the theme, character, plot, space and time setting, mandate, and point of view, shows a structure that influences one another. These elements cannot be separated from one another.